ANALISIS METALOGRAFI PELAT ELEMEN BAKAR U3Si2/Al DENSITAS 2,96 gU/cm3 PASCA IRADIASI - Ajiriyanto, Maman Kartaman; Ginting, Aslina Br.; Junaedi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Metallographic analysis of U3Si2/Al fuel element plate has been performed in hot cell. The purpose of metallographic analysis is to study changes in PEB U3Si2/Al microstructure and AlMg2 cladding thickness after irradiation in reactor until burn up of 56%. The fuel element plate of irradiated U3Si2/Al was cut in top, middle and bottom positions with each size around 5x5x1,37mm. Metallographic preparation starts from sample cutting using cutting machine with low speed and sample mounting, grinding and polishing in hot cell 104–105. Sample mounting was done by using resin for more than 10 hours followed by grinding with sandpapers up to grit size of 2400 and polishing with diamond paste of size 3 to 1 micron at a rotational speed of 150 rpm for 5 minutes. Microstructure observation was performed with optical microscope in hot cell 107 at 200 times magnification. Microstructure examination reveals U3Si2 particles with diverse forms and sizes, Al matrix and AlMg2 cladding were spread along the U3Si2/Al side. Microstructure observation of irradiated U3Si2/Al has not shown good result because only topography observation of U3Si2/Al meat, Al matrix and AlMg2 cladding can be done due to limited capability of the optical microscope in hot cell, where maximum magnification can be attained only at 200 times so that the phenomenon of interaction layer and small gas bubble cannot be observed. However, U3Si2/Al microstructure of 56% burnup, if compared to the microstructure of U3Si2/Al fuel element plate of 60% burnup from previous researcher, shows interaction between U3Si2 meat with Al matrix and the existence of layers with a thickness about 5 up to 20 microns. Meanwhile, the observed thickness of AlMg2 cladding is greater than 0.25 mm, which indicates that irradiation does not significantly change the thickness of AlMg2 cladding so that the overall irradiated U3Si2-Al still has good integrity and stability.